2019
DOI: 10.1101/735001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Mechanism of Action of Mitochondrial Therapeutic SS-31 (Elamipretide): Membrane Interactions and Effects on Surface Electrostatics

Abstract: SignificanceSzeto-Schiller (SS) peptides are among the most promising therapeutic compounds for mitochondrial dysfunction. However, the molecular target(s) and the mechanism of action of SS peptides are poorly understood. In this study, we evaluate the interaction of the lead compound SS-31 (Elamipretide) with mitochondrial and synthetic model membranes using a host of biophysical techniques. Our results show that SS-31 membrane interaction is driven largely by the negative surface charge of mitochondrial memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…It has recently been shown that SS-31 alters surface electrostatic properties of the mitochondrial inner membrane ( Mitchell et al, 2019 ). The consequences of this effect could include alteration of the channel ion gating properties of the ANT, including conformational changes secondary to enhanced supercomplex and ATP synthasome complex stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that SS-31 alters surface electrostatic properties of the mitochondrial inner membrane ( Mitchell et al, 2019 ). The consequences of this effect could include alteration of the channel ion gating properties of the ANT, including conformational changes secondary to enhanced supercomplex and ATP synthasome complex stability.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this directly affects stability of the synthasome components. Alternatively, the effect could be due to the change in inner membrane electrostatic properties that has recently been shown to result from incorporation of SS-31 into the inner membrane ( Mitchell et al, 2019 ), as this could indirectly stabilize the ATP synthasome.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the elamipretide effect of improving membrane integrity was even observed when cardiolipin levels in the in vitro system were lowered to levels consistent with those seen in Barth syndrome [58]. Furthermore, the elamipretide-mediated effects on membranes were observed across independent model systems where cardiolipin was oxidized or enriched with monolysocardiolipin, the immature form of cardiolipin found in Barth syndrome [57,59]. These studies suggest that mitochondrial structure and function are, as expected, interdependent and demonstrate that elamipretide targets mitochondrial membranes to stabilize cristae networks and improves bioenergetic function [58].…”
Section: Elamipretidementioning
confidence: 85%
“…1) leads to a restoration of healthy gene expression (within days) and improved cardiac and mitochondrial protein turnover (within weeks) [26,62]. Many mitochondrial functions, including oxidative phosphorylation, are strongly associated with the inner mitochondrial membrane [59]. The abnormal structure and function of the mitochondrial network is reflected by impaired mitochondrial cristae structure and loss of mitochondrial network connectivity.…”
Section: Elamipretidementioning
confidence: 99%
See 1 more Smart Citation